Pemberdayaan Perempuan dan Balita Melalui Asuhan Kebidanan Komunitas sebagai Upaya Meningkatkan Status Kesehatan Masyarakat - Ratna Ningrum, Riana; Rina Banne Ringgi; Ririn Rabbania; Septiani Dewi Putri; Aliviani Putri, Risma (Universitas Ngudi Waluyo, 2024)
Community Midwifery is a professional midwifery service aimed at the community with an emphasis on high-risk groups with an effort to achieve optimal health levels through disease prevention, health promotion, ensuring the affordability of needed health services and involving clients as partners in the planning, implementation and evaluation of midwifery services. Managing the care of ANC, PNC, BBL, Infant, Toddler, Reproductive Health and Family Planning in the community. Community midwifery practices can arouse community participation, so that people can overcome their health problems and find alternative solutions together. The implementation method used in this community service is health counseling which is given to 4 targets, namely pregnant women, postpartum mothers, toddlers and adolescents. However, the priority of the problem in RT 25 Graha Indah Village, North Balikpapan is the lack of knowledge about reproductive health in adolescents. Implementation on October 26, 2024. The participants of this counseling activity amounted to 34 teenagers. The activity was carried out in stages: (1) providing an explanation of the purpose of the activity; (2) distributing pre-tests to target adolescents; (3) providing health counseling on